2020
DOI: 10.1136/archdischild-2019-318627
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord milking in preterm infants: a systematic review and meta-analysis

Abstract: ObjectiveTo conduct a systematic review and meta-analysis of the efficacy and safety of umbilical cord milking in preterm infants.DesignRandomised controlled trials comparing umbilical cord milking with delayed cord clamping/immediate cord clamping in preterm infants were identified by searching databases, clinical trial registries and reference list of relevant studies in November 2019. Fixed effects model was used to pool the data on various clinically relevant outcomes.Main outcome measuresMortality and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 42 publications
(120 reference statements)
1
29
0
2
Order By: Relevance
“…This population was not included in our study, most of the premies we studied had a mean gestational age of 32 weeks where the risk has been reported to be lower [20]. A recent systematic review reports the risk of severe IVH in preterm infants <34 weeks gestational age [21]. Data on IVH are still limited in gestational groups greater than 28 weeks to confidently exclude any risk and unfortunately due to limitations in availability of cranial ultrasound in our setting, this study was unable to provide any further data on this outcome.…”
Section: Plos Onementioning
confidence: 99%
“…This population was not included in our study, most of the premies we studied had a mean gestational age of 32 weeks where the risk has been reported to be lower [20]. A recent systematic review reports the risk of severe IVH in preterm infants <34 weeks gestational age [21]. Data on IVH are still limited in gestational groups greater than 28 weeks to confidently exclude any risk and unfortunately due to limitations in availability of cranial ultrasound in our setting, this study was unable to provide any further data on this outcome.…”
Section: Plos Onementioning
confidence: 99%
“…При сцеживании в отличие от немедленного пережатия пуповины была меньше частота трансфузии ЭСК крови (ОР 0,56 (95% ДИ 0,43-0,73), p < 0,001), но не отмечалось улучшения клинических исходов. Таким образом, на основании имеющихся данных не рекомендуется проводить сцеживание пуповины у глубоконедоношенных новорожденных [30].…”
Section: сравнительный анализ частоты заболеваний при различных способах профилактики и лечения ран у исследуемых групп пациентовunclassified
“…(16) Previous studies have shown increased risk of severe IVH with UCM among very premature newborns (< 28 weeks). (17,18) 1. Anticipation, preparation and having trained providers working as a team are essential for newborn resuscitation.…”
mentioning
confidence: 99%